Treatment response and long-term survival in multiple myeloma in the GMMG-HD4 trial: neither profit all molecular entities alike, nor are remissions to different regimen equal - Seckinger, Anja; Salwender, Hans; Martin, Hans; Scheid, Christoph; Hielscher, Thomas; Bertsch, Uta; Hummel, Manuela; Jauch, Anna; Knauf, Wolfgang; Emde-Rajaratnam, Martina; Beck, Susanne; Neben, Kai; et al. (Blood, 2018)
IntroductionThe inclusion of "novel" agents including proteasome inhibitors or IMiD-derivatives in the treatment of multiple myeloma significantly improves patient survival. Results of several study groups suggest incorporating at least one "novel agent" in first-line treatment before and after high-dose chemotherapy (HDT) followed by autologous stem cell transplantation. Here we address four main questions: First, what determines (excellent) long-term survival for different treatment regimen? Second, can we show benefit of novel agents for all patients and molecular subentities, including low risk? Third, can the prognostic impact of molecular entities be explained by different association with response, proliferation, and renal impairment? Fourth, does it matter regarding long-term survival by which agents, i.e. "old" vs. "new", a response was reached?Patients and MethodsPatients were included in the prospective phase III HOVON-65/GMMG-HD4-trial (German part, n=354) randomizing VAD-induction, autologous tandem-transplantation and thalidomide-maintenance vs. PAD-induction, tandem-transplantation and bortezomib-maintenance. Plasma cells after CD138-purification were subjected to interphase fluorescence in-situ hybridization and gene expression profiling using Affymetrix U133 2.0 DNA-microarrays. Median follow-up (time to censoring) was 93 months.ResultsLow proliferation, revised-ISS I and cyto-ISS I delineate excellent long-term survival (70-75% after eight years, both arms). Molecular entities are associated with proliferation-rate, i.e. higher (del17p13, del8p21, del13q14, 1q21+, t(4;14)) or lower proliferation (hyperdiploidy), and response: bad response/survival in case of del17p, bad response/no survival impact (t(11;14)), and good response/bad survival (1q21+, t(4;14), and del13q), depending on the treatment regimen. Thus, it does not hold true that good response = good survival if patients are substratified according to their molecular background. Renal insufficiency is associated with 1q21+, del17p13, and t(4;14). For patients with ≥1 of the chromosomal aberrations del17p13, t(4;14), 1q21+ (i.e. cytogenetic high risk, 27.5% of patients) or renal insufficiency (10.6%), risk is abrogated; in absence of these risk features, no benefit could be shown. Patients reaching a near complete remission or better (≥nCR) with VAD-based regimen, HDT followed by thalidomide maintenance show significantly better survival compared to those reaching ≥nCR after bortezomib-based induction/HDT followed by bortezomib maintenance treatment.ConclusionsTaken together, adversely prognostic molecular entities are associated with proliferation but can show association with better or adverse remission. Bortezomib-based upfront treatment abrogates chromosomal high-risk aberrations and renal insufficiency; however, no long-term survival-benefit is evident for those without these risk factors or low proliferation, i.e. the majority of patients. Responses achieved by different regimen are not equal in transmission in long-term survival. Responses (≥nCR) are not equivalent regarding their biological and prognostic role in patients with different molecular background and different treatment regimen.Seckinger:Celgene: Research Funding; Sanofi: Research Funding; EngMab: Research Funding. Salwender:Novartis: Honoraria, Other: travel suppport, Research Funding; Amgen: Honoraria, Other: travel suppport, Research Funding; Bristol-Myers Squibb: Honoraria, Other: travel suppport, Research Funding; Celgene: Honoraria, Other: travel suppport, Research Funding; Takeda: Honoraria; Janssen: Honoraria, Other: travel support, Research Funding. Scheid:Celgene: Honoraria; Janssen: Honoraria. Knauf:Janssen: Consultancy; AbbVie: Consultancy; Celgene: Consultancy, Honoraria; Gilead Sciences: Consultancy; Roche: Consultancy; Amgen: Consultancy, Honoraria; Mundipharma: Consultancy. Duehrsen:AbbVie: Consultancy, Honoraria; Amgen: Research Funding; Janssen: Honoraria; Celgene: Honoraria, Research Funding; Roche: Honoraria, Research Funding; Gilead: Consultancy, Honoraria. Dürig:Roche: Honoraria, Speakers Bureau; Janssen: Consultancy, Honoraria; Celgene: Honoraria. Schmidt-Wolf:Janssen: Research Funding; Novartis: Research Funding. Haenel:Novartis: Honoraria; Amgen: Honoraria; Roche: Honoraria; Takeda: Honoraria. Raab:Novartis: Consultancy, Honoraria, Research Funding; BMS: Consultancy, Honoraria, Research Funding; Celgene: Consultancy, Honoraria; Amgen: Consultancy, Honoraria, Research Funding. Sonneveld:Janssen: Honoraria, Research Funding; Celgene: Honoraria, Research Funding; Amgen: Honoraria, Research Funding; Karyopharm: Honoraria, Research Funding; BMS: Honoraria, Research Funding. Blau:Celgene: Other: Advisory board, Research Funding; Janssen: Other: Advisory board, Research Funding; Amgen: Other: Advisory board; Takeda: Other: Advisory board; Novartis: Other: Advisory boards; BMS: Other: Advisory board. Hillengass:Takeda: Honoraria, Other: Advisory Board; BMS: Honoraria, Other: Advisory Board; Celgene: Consultancy, Honoraria, Other: Advisory Board, Research Funding; amgen: Consultancy, Honoraria, Other: Advisory Board; Sanofi: Research Funding; Janssen: Honoraria, Other: Advisory Board; Novartis: Honoraria, Other: Advisory Board. Weisel:Amgen, BMS, Celgene, Janssen, and Takeda: Honoraria; Amgen, Celgene, Janssen, and Sanofi: Research Funding; Amgen, BMS, Celgene, Janssen, Juno, Sanofi, and Takeda: Consultancy, Membership on an entity's Board of Directors or advisory committees. Goldschmidt:Chugai: Honoraria, Research Funding; Janssen: Consultancy, Honoraria, Research Funding; Novartis: Honoraria, Research Funding; Takeda: Consultancy, Research Funding; Sanofi: Consultancy, Research Funding; Mundipharma: Research Funding; Celgene: Consultancy, Honoraria, Research Funding; Bristol Myers Squibb: Consultancy, Honoraria, Research Funding; Amgen: Consultancy, Research Funding; Adaptive Biotechnology: Consultancy; ArtTempi: Honoraria. Hose:Celgene: Honoraria, Research Funding; EngMab: Research Funding; Sanofi: Research Funding.